OP13. Glioblastoma in the Older Person – how do we predict those who will benefit from treatment? - Lorimer, Dr Cressida (Neuro Oncol, 2017)
INTRODUCTION: Glioblastoma (GBM) is the commonest primary malignant brain tumour among the adult population. Incidence peaks in the 7th and 8th decades of life and as our global population ages, rates are increasing. GBM is an almost universally fatal disease with life expectancy in the range of 3–5 months amongst the elderly. There is a distinct lack of evidence to support treatment choices for elderly patients. Options include best supportive care, radiotherapy alone, chemotherapy alone or combined modality treatment, and emerging evidence indicates that MGMT promoter methylation status may be a useful biomarker. Crucially, however, methods and tools for holistic assessment of older patients with GBM prior to treatment decisions have been poorly researched. While multi-dimensional geriatric assessment has been shown to predict treatment tolerance and survival in other tumour types, these assessment tools are likely to be less valid within the GBM cohort because of the unique and potentially isolated deficits caused by the disease itself. In order to begin tackling this issue we performed a cross-sectional survey of UK based consultant neuro oncologists to obtain information about current practices for assessing elderly GBM patients. METHODS: A questionnaire was designed by the principal investigator and the validity of the questions was assessed by 3 consultant co-investigators from 3 different centres. The final version was distributed as an electronic survey to all practising consultant neuro-oncologists in England, Scotland, Wales and Northern Ireland. RESULTS: There were 56 respondents from a total of 93 recipients (60% response rate). All respondents confirmed that at least some patients aged 70 or over were referred to their clinics from the local multidisciplinary team meeting (MDT). Only 18% of consultants routinely performed a cognitive or frailty screening test at initial consultation. Of those who performed a screening test, the majority reported that the results of the test changed their treatment decision in approximately 50% of cases. Despite the publication of the NORDIC and NOA-08 trials, there was a marked difference in how responders ranked the importance of MGMT methylation status in making treatment decisions. 6% of responders did not routinely test for MGMT status whereas 48% felt that MGMT status was very or extremely important. When making treatment decisions, participants ranked performance status as the most important clinical factor. CONCLUSION: In the first survey of this kind, we have shown a marked disparity in assessment techniques across the UK. While performance status was ranked as the most important factor, we argue that it is a crude measure of vulnerability within this cohort. Elderly GBM patients represent a uniquely challenging clinical population because of the complexity of distinguishing neuro oncology related symptoms from general frailty. There is a need for specific geriatric assessment models tailored to the elderly neuro oncology population which could be used alongside existing and emerging molecular biomarkers to facilitate treatment decisions on an individual basis.